Nature and Society in D. H. Lawrence's travel book Sea and Sardinia - Matyáš, Jan (Univerzita Pardubice, 2023)
This thesis deals with nature and societal themes depicted in the travelogue Sea and Sardinia, and the fiction Lady Chatterley's Lover and Sons and Lovers. The first part of this thesis consists of an overview of islands and islandness, its definitions and problematics. The second part of the thesis explores the selected novels and scrutinises the selected topics connected to industrial society, its effects on nature, and man's connectedness to nature itself.
Příroda a společnost v cestopise Sea and Sardinia D. H. Lawrence
Keywords: Lawrence, D.H.; ostrovnost; příroda; společnost; industrialismus; Sardínie; Lawrence, D.H.; islandness; nature; society; industrialism; Sardinia